Profile identification of students' attitude towards statistics course: A case study in UiTM Pahang Branch (Raub Campus) / Nur Dalila Norshahidi ... [et al.] - Norshahidi, Nur Dalila; Ismail, Noor Halimatus Sa'diah; Zainal Abidin, Syazwani; Abd Razak, Nor Fatihah (Universiti Teknologi MARA, Perak, 2021)
This paper is concerned about the students' attitude from Faculty Business and Management in UiTM Pahang Raub Campus, towards the Statistics course. The objective of this study is to determine the mean difference of students' performance between gender, to identify students' attitude towards Statistics course and to profile the students' attitude towards Statistics course. The survey was retrieved from the Survey of Attitude Towards Statistics (SATS) instrument. The independence T- test and Mean Score was used to retrieve the results. The results show a difference of test scores between genders, in which female students show a greater performance compared to male students. In addition, students demonstrate a positive attitude towards Statistics courses through Mean Score of the component (Affective, Effort, Cognitive Ability and Value). Even though female students show an outstanding performance than male students in test scores, through profiling male students tend to be more positive in attitude to understand this subject better. Overall, those findings help instructors to improvise their teaching methodologies in making statistics courses more interesting to be learned.